The chemical properties of soil for alfalfa production after biofertiliser application - Lemes, Rodrigo Luis [UNESP]; Soares Filho, Cecilio Viega [UNESP]; Garcia Neto, Manoel [UNESP]; Heinrichs, Reges [UNESP] (Universidade Estadual de Londrina (UEL), 2013)
The objective of this study was to evaluate the use of biofertilisers for the production of alfalfa shoot, root and nodule dry matter, and also, to evaluate the chemical properties of the soil. This study was conducted in the greenhouse of the Support Department, Animal Production and Health, Faculty of Veterinary Medicine/UNESP, Aracatuba - SP, from May to October 2010. The experimental design was completely randomised with six biofertiliser doses (0, 25, 50, 100, 200 and 400 m(3) ha(-1)) and five replicates. The biofertiliser doses were the primary treatments and the cuts (five) were subplots. The cuts were performed, on average, every 27 days at 10 cm above the soil. At the end of the experiment, the roots, nodules and soil from all experimental units were collected for chemical analysis. We observed a linear increase in dry matter production of the shoots relative to the doses studied. The dry matter production of the roots and nodules was not significantly different. The chemical properties of the soil significantly improved for calcium and magnesium as well as the sum of bases and base saturation with biofertiliser application. Biofertilisers can be used for agricultural production and favourably alter the soil characteristics.
Keywords: Biofertiliser; Medicago sativa; Nitrogen; nodules; Rots